“Romantic Realism/Victorian Romance”: An Introduction to Four Provocations - Freedgood, Elaine; McLane, Maureen (Romanticism and Victorianism on the Net, 2013)
Might we, Romanticists and Victorianists, be or become one people? This cluster of essays, by Ian Duncan, Mary Favret, Catherine Robson, and Herbert Tucker, addresses longstanding and emergent cruxes in our collective scholarship, including questions of periodization, mediality, trans/nationality, genre, and mode. “Romance” and “realism” provide two provoking terms for thought. An introduction, by Elaine Freedgood and N. Maureen McLane, lays out axes of categorization, questions for pedagogy and the profession as well as intellectual and disciplinary genealogies. Duncan notes the insufficiency of such terms as “long nineteenth century” and proposes Walter Scott as one figure who teaches us how to think period as well as realism and romance; Favret addresses the romantic lecture and its current resonance in the age of MOOCs; Robson explores the nature of Victorian reading, and directions for Victorianist readings; Tucker meditates on the status of desire and marriage plots—Romantic and Victorian “conjugalities.”